SME's Innovative Performance in Indonesia: The Linkage between Innovation Culture and Production Performance - Ratni Prima Lita; Meuthia Meuthia; Ranny Fitriana Faisal; Sari Surya (International Journal of Supply Chain Management, 2018)
In a rapidly changing environment, fostering innovation plays a critical role for SMEs to enhance performance. The study investigates the linkage between innovation culture, process innovation, product innovation, innovative performance, and production performance in Indonesian SMEs creative industry. An empirical insight using quantitative method was conducted by distributing the data from a field survey. A cross-sectional data from 153 SMEs owners as the respondents have done to fill out the form of questionnaires. Data were analyzed by Structural Equation Modeling with smartPLS software. The result of this study found that not all hypotheses proposed are supported. Innovation culture has a significant and positive influence on process innovation and product innovation, while process innovation also has a significant and positive influence on product innovation. Moreover, process innovation affects innovative performance which ultimately influences towards production performance. However, product innovation had no significant effect on innovation performance. The results of this study make both theoretical and practical implications. Theoretically, the novelty of this research related to the innovation culture approach by focussing on the configurations of SMEs innovation activities and their performance implications was elaborated. Thus, it provides a model to demonstrate these configurations. Practically, through this study, SMEs owner has a critical role to encourage and support the new initiatives of employees in creating a unique product.